WOMEN’S NARRATIVES ON THE GREAT WAR IN SERBIAN POPULAR LITERATURE OF THE INTERWAR PERIOD (СASE OF МILICA JAKOVLJEVIĆ – МIR JАM) - Koch, Magdalena (Porównania, 2015)
The aim of this paper is to present women’s personal narratives which offer an alternative picture of the First World War in Serbian literature. Literary historians have not focused on this problem so far, whereas it would greatly enrich the literary representation of the Great War to add female perception and illustrate this historical cataclysm with women’s everyday war experience. The literary material analyzed here is the work by Milica Jakovljević (better known under the pseudonym Mir Jam), the author of popular literature in the interwar period. This paper contains an analysis of her three works, each belonging to a different genre: the drama Tamo daleko (‘There, Far Away’), the novel U slovenačkim gorama (‘In Slovenian Mountains’) and the autobiography Izdanci Šumadije (‘Offsprings of Šumadija’). The key categories applied in the discussion of Milica Jakovljević’s work are: women’s literature (women’s thematic and narrative perspective, women’s authorship and female recipient), popular literature/culture, microhistory and cultural memory.